IMPLEMENTASI PENDIDIKAN INKLUSI DI KOTA KEDIRI: STUDI KASUS DI SMP YBPK KEDIRI - Ninik Zuroidah dan Fathimatul Zahrol F (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
In order to pursue educational equity for Indonesian citizens , the government has issued a policy on inclusive educational programs in schools. The programs aim to provide for all children, including those with special needs. Schools that implement inclusive education should accommodate the students with special needs in terms of curriculum, teachers, lesson facilities, and learning activities. Based on a field research, this article examines the implementation of inclusive education in YBPK Junior High School Kediri, which is the first inclusive Junior High School in Kediri where most of students require special needs. This study revealed that through approriate plans and adjustment in materials and methods, the teachers are succesfull in increasing socialization of the students with special needs in the school.Keywords: Pendidikan Inklusi, SMP YBPK Kediri, Anak Berkebutuhan Khusus (ABK)